2008
DOI: 10.1088/0953-8984/20/15/155108
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermal stability criteria of Bi2O3–B2O3glasses

Abstract: Glasses with compositions xBi 2 O 3 -(100 − x)B 2 O 3 with 30 x 60 mol% have been prepared using the normal melt quenching technique. Infrared (IR) spectroscopy was used as a structural probe of the nearest-neighbor environment in the glass network. Assessment of the thermal stability of these glasses was achieved in terms of various simple quantitative methods based on the characteristic temperatures, such as the glass transition temperature, T g , the onset temperature of crystallization, T in , the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 41 publications
1
34
1
Order By: Relevance
“…The shoulder around 840 cm À1 becomes more predominant as the Bi 2 O 3 content increases and is related to the symmetrical stretching vibration of the Bi-O bonds in the [BiO 3 ] groups [11]. The strong band at $700 cm À1 is due to the bending vibration of B-O-B linkages of BO 3 units [9,25]. The weak band observed at $520 cm À1 is due to m 4 vibrations of BO 4 tetrahedra and the weak bands below 500 cm À1 are due to Bi-O vibrations [10,11].…”
Section: Ir Spectramentioning
confidence: 98%
“…The shoulder around 840 cm À1 becomes more predominant as the Bi 2 O 3 content increases and is related to the symmetrical stretching vibration of the Bi-O bonds in the [BiO 3 ] groups [11]. The strong band at $700 cm À1 is due to the bending vibration of B-O-B linkages of BO 3 units [9,25]. The weak band observed at $520 cm À1 is due to m 4 vibrations of BO 4 tetrahedra and the weak bands below 500 cm À1 are due to Bi-O vibrations [10,11].…”
Section: Ir Spectramentioning
confidence: 98%
“…It is suggested that the addition of Bi 2 O 3 to borate networks results in the formation of Bi-O-Bi bonds, leading to a dramatic improvement in the chemical durability and thermal stability of the borate glasses. 9 On the other hand, the presence of the [AlO 4 ] 4− tetrahedra of Al 2 O 3 in borate-based glasses causes the boron to remain trico-ordinated and, consequently, to a certain extent, helps to maintain the constancy of the glass structure. In boroaluminate glasses containing alkaline-earth modifier ions, B 3+ and Al 3+ compete for tetrahedral sites, with most going to Al 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…9 The glasses have loose-packed structure, are thermally unstable and have declining T g values. In the glasses studied, the values of T g decreased from 480 to 444 • C with the increase of Bi 2 O 3 content (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) is 159, for the present glasses (CBBO) reflecting the higher thermal stability than the other known Bi 2 O 3 -B 2 O 3 -based glasses. 15 The frequency (100 Hz-10 MHz) dependence of the dielectric constant (e 0 r ) and loss (D) at various temperatures (300-700 K) for the as-quenched samples is depicted in Figs. 2a and b, respectively.…”
Section: Resultsmentioning
confidence: 99%